Analysis of FET-PET imaging for target volume definition in patients with gliomas treated with conformal radiotherapy - Rieken, Stefan; Habermehl, Daniel; Giesel, Frederik L.; Hoffmann, Christoph; Burger, Ute; Rief, Harald; Welzel, Thomas; Haberkorn, Uwe; Debus, Juergen; Combs, Stephanie E. (Radiotherapy and Oncology, 2013)
Background and purpose Modern radiotherapy (RT) techniques such as stereotactic RT, intensity-modulated RT, or particle irradiation allow local dose escalation with simultaneous sparing of critical organs. Several trials are currently investigating their benefit in glioma reirradiation and boost irradiation. Target volume definition is of critical importance especially when steep dose gradient techniques are employed. In this manuscript we investigate the impact of O-(2-(F-18)fluoroethyl)-l-tyrosine-positron emission tomography/computer tomography (FET-PET/CT) on target volume definition in low and high grade glioma patients undergoing either first or re-irradiation with particles. Methods and material We investigated volumetric size and uniformity of magnetic resonance imaging (MRI)- vs. FET-PET/CT-derived gross tumor volumes (GTVs) and planning target volumes (PTVs) of 41 glioma patients. Clinical cases are presented to demonstrate potential benefits of integrating FET-PET/CT-planning into daily routine. Results Integrating FET-uptake into the delineation of GTVs yields larger volumes. Combined modality-derived PTVs are significantly enlarged in high grade glioma patients and in case of primary RT. The congruence of MRI and FET signals for the identification of glioma GTVs is poor with mean uniformity indices of 0.39. MRI-based PTVs miss 17% of FET-PET/CT-based GTVs. Non significant alterations were detected in low grade glioma patients and in those undergoing reirradiation. Conclusions Target volume definition for malignant gliomas during initial RT may yield significantly differing results depending upon the imaging modality, which the contouring process is based upon. The integration of both MRI and FET-PET/CT may help to improve GTV coverage by avoiding larger incongruences between physical and biological imaging techniques. In low grade gliomas and in cases of reirradiation, more studies are needed in order to investigate a potential benefit of FET-PET/CT for planning of RT. © 2013 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Boost irradiation; Delineation; FET; Glioma; Uniformity